(untitled) (Teresa Vigetti: Revista de Trabajo Social, 2025)
This article proposes to share some perspectives on the process of preparing register for social work students who are completing their academic internship. To this end, we recognize the contributions of the crossing of situated feminisms and decolonial studies, which promote situated thinking, the construction of objectivity without neutrality, as well as a careful look at the existing dehierarchizations and subordinations regarding gender, race, and class. Furthermore, we revisit the contributions of anthropology, where participant observation contributes to the necessary process of analytical reconstruction, which is related to the construction of mediations and a situated perspective. It also helps us consider "what are we registering?" and narrative modes themselves. The methodological principle of estrangement enables us to reflect on what distances are necessary, just as feminist epistemologies invite us to give place for "proximal distances." The distinction between field diary and field register is also borrowed from anthropology, and within the framework of the subject, it allows us to conceive of them as the place where the intervention takes shape, as well as constituting a fundamental tool that enables each student to build a leading role in their own learning process. Some suggestions are made to support teachers in the process of writing register, knowing that there are no recipes, but rather that it is a construction influenced by the unique and situated perspective of each student.